Enhanced Energy Transfer Performance in an Inclined Magneto-Convective Sutterby Ternary Hybrid Nanoflow: Application for Nano Diesel (Contemporary Mathematics, 2024)
This study investigates sodium alginate-based nano-lubricants with added copper and aluminum oxides. The thermal performance of nano (Al2O3), hybrid (Al2O3 + CuO) and ternary (Al2O3 + CuO + TiO2) nanofluids is studied and compared in this article. Due to the significant impact of higher stream rates, the ternary nanofluid is crucial in domains such as petroleum engineering. A Sutterby nanoflow model past a stretching sheet embedded in permeable media is considered. In this fluid, the effects of thermal radiation, hotness source/sink, inclined magneto-convection under Stefan blowing, and chemical reaction are assumed. The highest-order nonlinear partial differential equation is handled by utilizing the similarity function, producing a new set of ordinary differential equations. The derived equations are then quantitatively analyzed using the bvp4c approach in MATLAB.Graphical representations of several features for specific non-dimensional variables, including heat transfer, Sherwood, drag coefficient, velocity, temperature, and concentration, are presented. An increase in the thermal curve is observed due to the heat source/sink parameter; however, the Nusselt number exhibits the opposite pattern. The participation of Nb and the thermophoresis force led to greater thermal radiation. For Sc and Kr, the mass transfer ratio of the ternary nanofluid is lower. The results show very good congruence when compared to the literature. Our results also prove that the ternary hybrid nanofluid transfers more heat from the system than the hybrid or nanofluid. With an increase in Stefan blowing, the rate of energy and mass transfer rises, while the local skin friction coefficients show a tendency in the opposite direction.
Keywords: chemical reaction, inclined magnetic field, porous medium, sutterby nanoflow model, stefan blowing condition, thermophoretic process, thermalradiation, ternary nanofluid